Why we need ESS signalling theory. - Grafen, A; Johnstone, R (1993)
Evolutionarily stable strategy (ESS) models of biological signalling are important because the intimate coevolution of signalling and receiving strategies is complicated. Tentative results from a numerical study of error-prone signalling show the value of formal modelling. Error in perception can create discreteness in the distribution of signals produced, and so observed discreteness in nature may call for no more complicated explanation. Further developments in the theory of signalling may include a link with theories of aggression such as the sequential assessment game. The technical device of a 'scratch space' may allow a natural development of 'two-way' information games in which each contestant plays the roles of signaller and receiver simultaneously. This device may also incidentally derive mental states from purely strategic considerations.